Basics Telecommunication System Covers Working Principles and Emerging Problems - Que Duc Chinh; Bui Thuan Nguyen (Newinera Publisher, 2020)
This article discusses the basics of the telecommunications system covering developments, working principles and emerging problems in telecommunications. The telecommunications system is all elements of both telecommunications infrastructure, equipment, facilities and infrastructure, as well as telecommunications operators, so that long-distance communication can be carried out. During the journey the information will pass through various media with different characteristics. So that it allows the occurrence of high delays and large packet loss, all of which will reduce the quality of the information received. The quality of the transmission medium determines the quality of the information received. Because as long as it is in the media, it is certain that the information will experience damping which will reduce the quality of the information. In order to communicate properly, the channel provided is not only physical media but also logical lines (frequency channels), considering that these frequency channels are expensive and limited.